2019
DOI: 10.1186/s13287-019-1267-0
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic epithelial cell transplantation promotes neurogenesis and ameliorates social deficits in BTBR mice

Abstract: Background Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairments in social interactions and communication and stereotypical patterns of behaviors, interests, or activities. Even with the increased prevalence of ASD, there is no defined standard drug treatment for ASD patients. Currently, stem cells, including human amniotic epithelial cell (hAEC) transplantation, seem to be a promising treatment for ASD, but the effectiveness needs to be verified, and the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Autism spectrum disorder (ASD) is a complicated disorder in neural development involved in social connectivity and interaction [ 102 ]. Zhang et al observed that the intraventricular injection of hAESCs alleviated the social deficits by rescuing the function of hippocampus in BTBR mice [ 103 ]. Mucopolysaccharidosis type 1 (MPS1) is characterized by the dysfunction of lysosomal storage and is often accompanied by neurological degeneration [ 104 ] and hAESCs injection ameliorated the ability of sensorimotor coordination in MPS1 mice [ 105 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a complicated disorder in neural development involved in social connectivity and interaction [ 102 ]. Zhang et al observed that the intraventricular injection of hAESCs alleviated the social deficits by rescuing the function of hippocampus in BTBR mice [ 103 ]. Mucopolysaccharidosis type 1 (MPS1) is characterized by the dysfunction of lysosomal storage and is often accompanied by neurological degeneration [ 104 ] and hAESCs injection ameliorated the ability of sensorimotor coordination in MPS1 mice [ 105 ].…”
Section: Cell-based Therapy With Human Amnion-derived Stem Cellsmentioning
confidence: 99%
“…The hAM has been studied since many years and is used in the treatment of burns, skin defects, and corneal injuries [15,16]. Because of their antiinflammatory and immunomodulatory properties, human amniotic cells have been considered as valid candidates for cell therapy in several degenerative disorders [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…General exploratory locomotion in the open field apparatus was evaluated according to our previous described ( Zhang et al, 2019 ). During the test, a mouse was placed in the center of open field box and allowed to explore for 30 min.…”
Section: Methodsmentioning
confidence: 99%